LncRNA HAS2-AS1 Promotes Glioblastoma Proliferation by Sponging miR-137 - Lu, Yalin; Guo, Gaochao; Hong, Rujun; Chen, Xingjie; Sun, Yan; Liu, Fang; Zhang, Zhimeng; Jin, Xun; Dong, Jun; Yu, Kai; Yang, Xuejun; Nan, Yang; et al. (Frontiers in Oncology, 2021)
Background: Glioblastoma multiform (GBM) is the most malignant tumor type of the central nervous system and has poor diagnostic and clinical outcomes. LncRNAs have been reported to participate in multiple biological and pathological processes, but their underlying mechanism remains poorly understood. Here, we aimed to explore the role of the lncRNA HAS2-AS1 in GBM. Methods: GSE103227 was analyzed, and qRT-PCR was performed to measure the expression of HAS2-AS1 in GBM. Fluorescence in situ hybridization (FISH) was performed to verify the localization of HAS2-AS1. The interaction between HAS2-AS1 and miR-137 was predicted by LncBook and miRcode followed by dual‐luciferase reporter assays, and the relationships among HAS2-AS1, miR-137 and LSD1 were assessed by Western blot (WB) and qRT-PCR. Colony formation and CCK-8 assays were performed as functional tests. In vivo, nude mice were used to confirm the function of HAS2-AS1. Results: HAS2-AS1 expression was upregulated in GBM cell lines, and HAS2-AS1 was localized in mainly the cytoplasm. In vitro, high HAS2-AS1 expression promoted proliferation, and knockdown of HAS2-AS1 significantly inhibited proliferation. Furthermore, HAS2-AS1 functioned as a competing endogenous RNA (ceRNA) of miR-137, leading to the disinhibition of its downstream target LSD1. The miR-137 level was downregulated by HAS2-AS1 overexpression and upregulated by HAS2-AS1 knockdown. In a subsequent study, LSD1 expression was negatively regulated by miR-137, while miR-137 reversed the LSD1 expression levels caused by HAS2-AS1. These results were further supported by the nude mouse tumorigenesis experiment; compared with xenografts with high HAS2-AS1 expression, the group with low levels of HAS2-AS1 exhibited suppressed proliferation and better survival. Conclusion: We conclude that lncRNA HAS2-AS1 promotes proliferation by functioning as a miR‐137 decoy to increase LSD1 levels and thus might be a possible biomarker for GBM.